Incorporation of Poly(propylene succinate-co-glycerol succinate) (PPSG) as a Renewable Additive in Electrospun PCL Fibers with Bioactive Glass Particles for Soft Tissue Engineering - Dourado Fernandes, Clara; Grünewald, Alina; Hadzhieva, Zoya; Oechsler, Bruno F.; Sayer, Claudia; Hermes de Araújo, Pedro H.; Boccaccini, Aldo R. (ACS Applied Bio Materials, 2025)
As human longevity increases, the prevalence of age-related pathologies grows, driving the need for advances in regenerative medicine. This research evaluates poly(propylene succinate-co-glycerol succinate) (PPSG) as a renewable additive in electrospun polycaprolactone (PCL) mats, to develop biodegradable and biocompatible scaffolds incorporating 45S5 bioactive glass (BG) particles of size ∼4 μm. Electrospinning solutions with 20% (w/v) acetic acid were used, with PPSG proportions of 5%, 10%, and 15% by weight. Additionally, BG particles were incorporated at 5, 15, and 30 wt % to enhance bioactivity. Uniform fibers were achieved with 10% PPSG at 0.4 mL/h and 15 kV, yielding bead-free structures. PPSG increased fiber diameter and mechanical properties, with Young’s modulus (E) rising from 1.7 ± 1 MPa (pure PCL) to 8.8 ± 1.5 MPa (PCL/20PPSG). Ultimate tensile strength (Σ) improved from 0.4 MPa (PCL) to 1.5 MPa (PCL/10PPSG). BG incorporation enhanced bioactivity but reduced mechanical stability due to particle distribution. Samples containing 15% BG exhibited significantly increased NHDF cell viability, and hydrophilicity improved with PPSG (reduced from 110° to 28 ± 3°). Biodegradability testing revealed a 45% ± 5 mass loss for 10% PPSG fibers over 35 days. The PCL/PPSG/BG composite demonstrates enhanced mechanical strength, bioactivity, and cell viability, making it a promising candidate for soft tissue engineering and regenerative medicine.
CRIS-Team Scopus Importer:2025-06-13
Keywords: 45S5 bioglass; Biodegradability; Composite fibers PPSG; Hydrophilicity; Sustainable electrospinning